The Effectiveness of Asynchronous Learning Community on ESL learners’ skills acquisition - Jayanthi Muniandy,; Malini Ganapathy, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study investigated the impact of an asynchronous learning community (ALC) on English as a second language (ESL) learners’ skills acquisition. The ALC was designed by incorporating the community of inquiry (CoI) framework, which highlights cognitive, social, and teaching presence. The participants of this study consisted of 24 ESL learners and four ESL educators, and they were selected using a purposive sampling method. Focus groups and one-to-one semi-structured interviews were conducted to gather data. The responses were analysed using thematic analysis. The results showed that opinion-based discussions play an essential role in enhancing learners’ skills, particularly their higher-order thinking skills. The study also identified some challenges ESL learners encountered in the ALC, such as improper time management skills, lack of participation, and a sense of isolation. Therefore, some effective strategies were proposed to overcome these challenges. The study recommends that the ALC approach that integrates the CoI framework should be embedded in the ESL curriculum to develop learners’ skills and foster a sense of community in the virtual learning environment. This approach can lead to better outcomes for learners in terms of skill acquisition and their ability to succeed in academic and professional settings.